Reconstruction of engineered yeast factory for high yield production of ginsenosides Rg3 and Rd - Lin, Yuan; Wang, Yi Na; Zhang, Guang Hui; Chen, Geng; Yang, Qing Hui; Hao, Bing; Yang, Sheng Chao (Frontiers in Microbiology, 2023)
Panax notoginseng is one of the most valuable traditional Chinese herbs. The main active ingredients, dammarane-type ginsenosides, show multiple pharmacological activities. Recently, the key UDP-dependent glycosyltransferases (UGTs) involved in the biosynthesis of common ginsenosides have been widely studied. However, only a few UGTs that catalyze ginsenoside formation have been reported. This study further investigated the new catalytic function of 10 characterized UGTs from the public database. PnUGT31（PnUGT94B2） and PnUGT53 （PnUGT71B8）exhibited promiscuous sugar-donor specificity of UDP-glucose and UDP-xylose, which could catalyze the glycosylation of C20-OH sites and elongation of the sugar chain at the C3 and/or C20 sites. We further analyzed the expression patterns in P. notoginseng and predicted the catalytic mechanisms of PnUGT31 and PnUGT53 using molecular docking simulations. Moreover, different gene modules were built to increase the yield of ginsenosides in engineered yeast. The metabolic flow of the proginsenediol (PPD) synthetic pathway was enhanced by LPPDS gene modules based on the engineered strain. The resulting yeast was constructed to produce 1.72 g/L PPD in a shaking flask, but cell growth was significantly inhibited. EGH and LKG gene modules were constructed to achieve high-level production of dammarane-type ginsenosides. The production of G-Rg3 controlled by LKG modules increased 3.84 times (254.07 mg/ L), whereas the G-Rd titer reached 56.68 mg/L after 96 h in shaking flask culture under the control of all modules, both of which yielded the highest values for known microbes.